PERSENTASE VARIASI FENOTIP ANTIGEN ABO DAN ANTIGEN DUFFY PADA MAHASISWA AKADEMI BAKTI KEMANUSIAAN PALANG MERAH INDONESIA ANGKATAN SATU - Diana Novita; Gita Rahvita (Ensiklopedia of Journal, 2019)
Every person has a blood type system and different types of antigens on the surface of red blood cells. Before the blood is transfused into the patient's body, a pre-transfusion examination must be performed and a transfusion reaction is detected which is marked by antibodies to red blood cells. To prevent transfusion reactions by administering appropriate and safe blood. One of them is by checking ABO blood group first. Then another blood type examination can be performed which can also cause a transfusion reaction, but this has not been possible because of the limitations of routine pre-transfusion examinations performed for patients who do not have specific antibodies with donor antigens. To find out the percentage variation of ABO antigen and Duffy antigen phenotypes at the Indonesian Red Cross Human Rights Academy Students Force One. Analytical Observation. Sample of the Indonesian Red Cross Indonesian Human Services Academy Student Force One. Forty samples of the 1st batch of ABK PMI students with unknown ABO antigen type and Fya or Fyb antigen type were tested for phenotyping using Direct Coomb’s Test and Indirect Coomb's Test (ICT) methods. From the results of the phenotyping examination, the results showed that blood group A was 11 samples (27%), blood group B 12 samples (30%), blood group AB 2 samples (5%), blood group O 15 samples (38%) and Fya 37 samples ( 92%) and Fyb 3 (8%) of 40 samples (100%). It can be concluded that the majority have blood type O blood and have Fya antigens on the sample of ABK PMI student class one. Phenotyping is expected to reduce the risk of transfusion reactions by providing donor blood that has an antigen that is not specific to the antibodies that the patient has so that the transfusion reaction does not occur.